Effects of the addition of hydrocortisone aceponate to intramammary procaine penicillin for treatment of intramammary infections in dairy cattle - R.R. Munn; S. McDougall (Journal of Dairy Science)
ABSTRACT: The objective of this study was to assess the effects of the addition of the corticosteroid hydrocortisone aceponate (HCA) to a procaine penicillin G intramammary infusion on clinical outcomes and bacteriological cure rates of naturally occurring bovine mastitis. This prospective, randomized, superiority and noninferiority, blinded, positive-controlled intervention study included clinical and subclinical arms. For the clinical arm, cows were randomly assigned within farm to be treated with penicillin and HCA (IVP) or penicillin alone (CP) on 3 occasions at 24-h intervals following collection of a milk sample. Cows were enrolled over 2 yr; 65 quarters (59 cows) in yr 1, and 66 quarters (61 cows) in yr 2. For the subclinical arm, cows were enrolled if they had a SCC > 200,000 cells/mL at the most recent DHI test and had no signs of clinical mastitis. Following bacterial isolation from a milk sample, quarters were enrolled and treated. Cows (n = 410; 715 quarters) were blocked within herd by age, ranked on SCC, and randomly assigned in a 2 × 2 factorial arrangement to be treated on 3 occasions with IVP or CP at 12- or 24-h intervals. Milk samples for microbiology and SCC were collected at intervals up to 28 d after initiation of treatment. At the same time, quarters of clinical cases were assessed for the presence of clots in milk and for heat or swelling. Streptococcus uberis was the most common isolate before treatment in the clinical arm, and Corynebacterium spp. and NAS the most common in the subclinical arm. Bacteriological cure was defined as nonisolation of the bacterial species present pretreatment from any sample posttreatment. The bacteriological cure rate did not differ between treatment groups in the final multivariate model in the clinical or subclinical arm. The bacteriological cure rate of IVP was noninferior to that of CP in the subclinical arm, and treatment at 24-h intervals was noninferior to treatment at 12-h intervals. In the clinical arm, posttreatment SCC were lower for quarters in the IVP than the CP group 14, 21, and 28 d after initiation of treatment. Quarter-level SCC did not differ between treatment groups in subclinically infected quarters. For clinical cases, the proportion of quarters with heat or swelling was reduced following treatment with IVP compared with CP. We do not advocate the routine treatment of subclinical mastitis during lactation and did not demonstrate a benefit of corticosteroid inclusion in these subclinical cases. We conclude that the bacteriological cure rate of subclinical mastitis was noninferior following treatment with penicillin and HCA compared with penicillin alone and for 24-h compared with 12-h treatment intervals. There was evidence of reduced severity of local inflammation in cases of clinical mastitis when HCA was combined with penicillin compared with treatment with penicillin alone.